Affinity‐based proteomics reveals novel targets of inositol pyrophosphate (5‐IP7)‐dependent phosphorylation and binding in Trypanosomacruzi replicative stages. Issue 5 (21st January 2021) - S. Mantilla, Brian; Kalesh, Karunakaran; Brown, Nathaniel W.; Fiedler, Dorothea; Docampo, Roberto
Abstract: Diphosphoinositol‐5‐pentakisphosphate (5‐PP‐IP5 ), also known as inositol heptakisphosphate (5‐IP7 ), has been described as a high‐energy phosphate metabolite that participates in the regulation of multiple cellular processes through protein binding or serine pyrophosphorylation, a posttranslational modification involving a β‐phosphoryl transfer. In this study, utilizing an immobilized 5‐IP7 affinity reagent, we performed pull‐down experiments coupled with mass spectrometry identification, and bioinformatic analysis, to reveal 5‐IP7 ‐regulated processes in the two proliferative stages of the unicellular parasite Trypanosoma cruzi . Our protein screen clearly defined two cohorts of putative targets either in the presence of magnesium ions or in metal‐free conditions. We endogenously tagged four protein candidates and immunopurified them to assess whether 5‐IP7 ‐driven phosphorylation is conserved in T. cruzi . Among the most interesting targets, we identified a choline/ o ‐acetyltransferase domain‐containing phosphoprotein that undergoes 5‐IP7 ‐mediated phosphorylation events at a polyserine tract (Ser 578‐580 ). We also identified a novel SPX domain‐containing phosphoribosyltransferase [EC 2.7.6.1] herein termed as TcPRPPS4. Our data revealed new possible functional roles of 5‐IP7 in this divergent eukaryote, and provided potential new targets for chemotherapy. Abstract : Lysates prepared from amastigotes and epimastigotes in the presence of magnesium ions or EDTA (i) were incubated with 5PCP‐IP5 or control reagent (ii). Eluted proteins were identified by mass spectrometry (iii) and GO‐terms analysis was done for all the resultant dataset hits (iv). Based on protein identification data, some targets were chosen for validation in vitro (v).